Responses of young rams to level of hydrolised feather meal subtitution in ration - Puastuti, Wisri; Mathius, I-Wayan (Indonesian Animal Sciences Society, 2008)
Feather meal contains more than 90% protein that most of this protein (70%) are ruminally undegradable, therefore it is a potential source of by pass protein. The study was done to evaluate the response of young rams to hydrolised feather meal (HBA) substitution in ration. Twenty five young rams aged 7-8 months, with average body weight of 21.16 Â± 2.47 kg were used in this study. This study was conducted based on ramdomized block design and the rams were grouped into 5 groups based on body weight. The ration consisted of 30% grass and 70% feed supplement on dry matter basis. Feed supplement of the control diet (R0) contained 72% of total digestible nutrient (TDN) and 15% ofÂ total crude protein (CP), whereas R1-R4 were the improved rations that contained 75% of TDN and 18% of CP. HBA was used to substitute feed protein and as by pass protein source. The HBA substitution was done in 5 levels, namely: R0 = grass + feed supplement with 0% HBA; R1 = grass + feed supplement with 1.1% HBA; R2 = grass + feed supplement with 2.2% HBA; R3 = grass + feed supplement with 4.4% HBA and R4 = grass + feed supplement with 8.5% HBA. The study was conducted for 12 weeks. The results showed that the increase of CP in ration and HBA substitution did not affect dry matter (DM), organic matter (OM) consumption, as well as DM, OM and CP digestibility. The substitution of HBA in ration significantly increased CP consumption of ram fed R1, R2, R3 and R4 compared to R0 (143.86; 142.58; 147.46; 134.43 vs 109.98 g/head). The level of NH3-N in rumen fluid was significantly (P<0.01) affected by CP in the ration and HBA substitution. On the other hand total VFA and molar volatile fatty acids were not different except for molar isobutirat. The value of N retention and average daily gain (ADG) were affected (P<0.05) by level of CP and subtitution HBA in ration. The highest ADG value was resulted by rams received R2 diet (133.77 g/head). It was concluded that 2.2% HBA substitution in ration gave the best response on consumption, digestion, rumen fermentation, N retention and ADG. Key Words: Hydrolised Feather Meal, Substitution, Ram